Comparative study on the effects and efficiencies of three sublimation drying methods for mushrooms - Xu, Duan; Wei, Liu; Guangyue, Ren; Wenchao, Liu; Yunhong, Liu (International Journal of Agricultural and Biological Engineering, 2015)
Freeze drying (FD) yields the best quality of dried mushrooms but needs long drying time and higher cost. Air drying (AD) gives relatively poor product quality. In order to achieve faster drying along with high product quality, microwave freeze drying (MFD) and atmospheric freeze drying (AFD) were developed to dry mushrooms. By comparison of three sublimation drying processes, it was concluded that FD could lead to the best product quality, but cost the highest energy consumption. AFD mushrooms had the worst quality and longest drying time, but the lowest energy consumption. Compared with FD and AFD, MFD could get relatively acceptable quality and drying efficiency. As a result, MFD can be used to replace traditional FD, and AFD also should be popularized because of its low energy consumption. DOI: 10.3965/j.ijabe.20150801.012 Citation: Duan X, Liu W, Ren G Y, Liu W C, Liu Y H. Comparative study on the effects and efficiencies of three sublimation drying methods for mushrooms. Int J Agric & Biol Eng, 2015; 8(1): 91-97.